Service Quality and Punctuality of Indonesian Railfood Customer Online System - Muhammad Raisa Permana Sakti; Syahputra Syahputra; Mahir Pradana (Politeknik Pertanian Negeri Samarinda, 2023)
This study aims to analyze the effect of Indonesian Railway Company (PT KAI)'s service quality, especially the punctuality of travel on railroad customer satisfaction. This study also aims to examine the effect of timeliness variables on customer satisfaction. The data used in this study is a combination of primary data and secondary data where the author will use the survey method as primary data and data on the timeliness of train travel, especially train travel to and from Bandung Station as secondary data. The data analysis technique used in this research is quantitative by using a systematic literature review in terms of bibliometric analysis to review published research on the topics discussed. The explanation for this is the result of the punctuality of train travel on railroad customer satisfaction.